Direction Structure of the Imaginary and Interpretation Controversy in the Theatre Reception "Mukashafat" Play -A Model: ثابت رسول جواد (Al-Academy, 2019)
The current research deals with the argument of delusion and interpretation in the direction structure and its reflected impact in the reception activity and the amount of conceptual displacement it is subjected to in an aesthetic approach to abstract conceptual definitions of the reception activity , by the effect of this dialectic in the direction structure, which can be summed up by the following question: (What are the characteristics of the direction structure of the imaginary and what is the argument of interpretation in the theatre reception activity?) in order to stand on the aesthetic framework and conceptual definition of the direction structure in the controversy of interpretation and imagination, and its impact on the conceptual and procedural definition of the theatre reception activity, through monitoring the repercussions of this controversy of the direction structure in the theatre reception activity , which limited the research with a pivotal aim: (Showing the activity of the imagination and interpretation controversy and the direction structure of the visualizer, and monitoring its aesthetic impact on the theatre reception concept). The research comes up within the limits set forth in its methodological framework, to analyze the studied phenomenon in order to identify it, conceptualize it, and employ it procedurally. The research consists of three frameworks: The methodological framework in which the researcher identified the problem of the research, its importance, the need for it, its purpose, and its limits, as well as defining its terms procedurally. The theoretical framework is of two axes: the first is the axis of the argument of delusion and interpretation in the direction structure, and the second axis is the controversy of delusion and interpretation in the theatre reception. The procedural framework included the researcher's procedures in applying the theoretical framework indicators to his chosen sample, namely the play "Mukashafat" (confessions) to monitor the conceptual effect of the controversy of interpretation and delusion in the direction structure, on the theatre reception concept. The research came up with a number of conclusions, the most important of which are: the theatre reception is a controversial act, in which the debate moved towards the activity of delusion and its criterion is the achievement of the assumption, and the activity of interpretation and its criterion is the achievement of the discovery.